Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.2307/1370134
|View full text |Cite
|
Sign up to set email alerts
|

Egg Removal by Brown-Headed Cowbirds: A Field Test of the Host Incubation Efficiency Hypothesis

Abstract: Abstract. Brown-headed Cowbirds (Molothrus ater) often remove host eggs, usually to the detriment of the host's reproductive success. We tested the hypothesis that host egg size and number influence the incubation efficiency of a parasitic egg. A single House Sparrow (Passer domesticus) or Brown-headed Cowbird egg was placed in each host nest (addition), and in some nests a host egg was removed as well (addition/removal). Hatching success and incubation length were measured to determine whether host-egg remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…We found no difference in the hatching success of Shiny Cowbird eggs in nests with 1–3 host eggs (i.e., nests with 0–2 host eggs punctured). Our results agree with those of Wood and Bollinger (1997) and McMaster and Sealy (1997), but these studies involved hosts either similar in size or smaller than the brood parasite. In these species, the removal or puncture of host eggs would be less critical for the parasite because their larger eggs would still contact the host's brood patch (Peer and Bollinger 1997, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found no difference in the hatching success of Shiny Cowbird eggs in nests with 1–3 host eggs (i.e., nests with 0–2 host eggs punctured). Our results agree with those of Wood and Bollinger (1997) and McMaster and Sealy (1997), but these studies involved hosts either similar in size or smaller than the brood parasite. In these species, the removal or puncture of host eggs would be less critical for the parasite because their larger eggs would still contact the host's brood patch (Peer and Bollinger 1997, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this prediction, Peer and Bollinger (1997) found that eggs of Brown-headed Cowbirds translocated to nests of a host larger than the parasite (Common Grackle, Quiscalus quiscula) did not hatch when clutches contained four to six eggs, but hatched when clutches had three or fewer eggs. In contrast, studies of host species either similar in size or smaller than Brownheaded Cowbirds indicate that removal of host eggs did not increase hatching success of parasite eggs (Wood andBollinger 1997, McMaster andSealy 1997). Egg punctures could have the same effect as egg removal by a parasite if hosts remove punctured eggs as a result of nest sanitation (Kemal and Rothstein 1988).…”
Section: Resumen Función De La Picadura De Huevos Por Parte Del Tordmentioning
confidence: 99%
“…The extra egg could decrease the incubation e¤ciency of the enlarged clutch (Davies & Brooke 1988). However, evidence in support of this hypothesis is not conclusive (Lerkelund et al 1993;McMaster & Sealy 1997;Wood & Bollinger 1997). In addition, a complete clutch would represent a competitive environment for the cowbird chick unless some of the host eggs were destroyed (Scott 1977;Blankespoor et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Cowbirds adversely affect the breeding success of their hosts through predation (McLaren and Sealy 2000), egg punctures (Massoni and Reboreda 2002), ejection of eggs and nestlings (Dearborn 1996, Wood and Bollinger 1997, Granfors et al 2001 and competition between nestlings (Dearborn 1998, Lichtenstein andSealy 1998). Parasitism rates in localities with high cowbird density can reach more than 90% (Payne 1997, Smith 1999, and severely reduce the reproductive output of host species.…”
Section: Introductionmentioning
confidence: 99%